Measuring and Modeling the Effects of Long-Term Buyer-Seller Relationships in Corporate Financial Services Markets - REDDY, Srinivas K. (Institutional Knowledge at Singapore Management University, 1999)
This paper focuses on attempting to identify and model the role that the long-term relationship plays in affecting future sales versus the roles of other such forces as product performance, sales activities, and price. A conceptual model of the long-term relationship is developed and empirically tested on data obtained from top level financial executives of 123 “important” customers of a major money center commercial bank. A structural equation model using multiple indicators is developed and estimated. Results indicate knowledge and perception of actively seeking customer's business affects the longevity of the relationship. Competitive pricing and past usage improve relative perceived performance. In turn, relative perceived performance and relationship longevity are positively related to future usage.